Agricultural Extension and Market-Led Agrarian Reform: Findings from an Exploratory Case Study in Limpopo Province, South Africa - Daniel Tobin; Thomas Bruening; Mark Brennan; Brad Olson (Journal of International Agricultural and Extension Education, 2012)
n 1994, as South Africa was transitioning out of the apartheid era, the new, democratically elected government was forced to confront a largely polarized agricultural sector. Colonial rule and apartheid policies had systematically dispossessed the African majority from land. At the end of apartheid, the white minority, comprising less than 10% of the population, controlled 87% of total agricultural land. To confront the harsh realities of food insecurity and poverty, South Africa’s post-apartheid democracy implemented land and agrarian reform policies. The purpose of this study was to understand the experiences and perceptions regarding these policies of emerging black farmers and agricultural extension officers in Limpopo Province, South Africa. The province has been an active participant in land and agrarian reform initiatives, but over 70% of resettlement projects have been deemed as not functioning. With such a high failure rate, the experiences of the people most directly impacted by reform initiatives in Limpopo can help clarify those elements of policy that are currently working and those that are not. This research utilized a qualitative case study approach to data collection. Analysis of data identified a series of consistent themes: Dependency, Knowledge and Skills, Networks, and Realistic Expectations. Based on these findings, a series of implications and recommendations regarding future research and agricultural extension programming are presented.
Keywords: Extension; Governmental Organizations; Case Study Research; Qualitative Research; Farmers; Social Change